2017
DOI: 10.1007/s10815-017-1049-5
|View full text |Cite
|
Sign up to set email alerts
|

Should intrauterine human chorionic gonadotropin infusions ever be used prior to embryo transfer?

Abstract: Intrauterine hCG at the time of ET not only seems to have no benefit, but rather a negative effect in fresh ETs and those without RIF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…A retrospective case–control study conducted at a multi-site private IVF clinic with 34,259 ETs of which 656 received intrauterine hCG infusions, reported that intrauterine hCG injection before ET not only seemed to have no benefit, but had a negative effect on fresh ETs [29]. Intrauterine hCG administration in fresh ETs was associated with a lower clinical-pregnancy rate and a downward trend in the live birth rate.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective case–control study conducted at a multi-site private IVF clinic with 34,259 ETs of which 656 received intrauterine hCG infusions, reported that intrauterine hCG injection before ET not only seemed to have no benefit, but had a negative effect on fresh ETs [29]. Intrauterine hCG administration in fresh ETs was associated with a lower clinical-pregnancy rate and a downward trend in the live birth rate.…”
Section: Discussionmentioning
confidence: 99%
“…But, Hong et al and Volovsky et al reported that intrauterine hCG seemed to have no benefit to clinical pregnancy rates, and in one meta‐analysis did not support the use of intrauterine hCG administration before embryo transfer. However, in another meta‐analysis found that women may benefit from intrauterine hCG injection before embryo transfer in IVF.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Hong et al mixture by dissolving 20 000 IU of urinary hCG powder with 0.8 mL of ET media, only 20 μL mixture was infused on the ET day. And in the study by Volovsky et al, dilution of 1500 IU of hCG in 125 μL of blastocyst media. Of this, 40 μL was then infused into the uterus 10 minutes to immediately prior to ET.…”
Section: Discussionmentioning
confidence: 99%
“…This includes the fusion of cytotrophoblast cells into the multinuclear structure of the syncytiotrophoblast (15), the formation of the umbilical circulation in villous tissue and the formation of the umbilical cord (16,17), the growth of fetal organs (18), the contribution to angiogenesis by forcing the development and growth of uSA (19)(20)(21) and the suppression of myometrial contractions (22). Thereby, hCG targets several molecules that are involved in decidualization, implantation, vascularization and tissue remodeling such as prolactin, insulinlike growth factor binding protein-1, macrophage colony stimulating factor, leukemia inhibitory factor (LIF), vascular endothelial growth factor (VEGF), matrix metalloproteinase (MMP)-9, tissue inhibitors of MMPs (TIMPs), galectin-3, and glycodelin (23)(24)(25)(26) (Figure 1B). H-hCG is produced by cytotrophoblast cells and is the most abundant hCG isoform around implantation (27).…”
Section: Hcg In Embryo Implantation and Placentationmentioning
confidence: 99%